(untitled) (Avocetta, 2025)
The Birds-of-Paradise (BoPs), celebrated for their exquisite plumage and significant historical allure, have faced threats from deforestation and hunting, necessitating ongoing conservation efforts. This study employs bibliometric analysis to examine the scientific literature on BoPs from 1862 to 2023, focusing on publication trends, influential countries, institutions, authors, and funding sources. By employing the Scopus database and VOSviewer for data visualisation, we have successfully identified a total of 255 publications, which include articles, reviews, and a variety of document types. Overall, the species of the genus Paradisaea are the most discussed. From a total of 44 species, only one species of BoPs is highlighted among all the papers examined using VOSviewer: Lophorina superba (n=14). This suggests that many other BoPs species have not received sufficient research attention. The analysis reveals a gradual increase in research interest since the 1970s, with the United States, Australia, and the United Kingdom leading in publication output. The study also maps the evolution of research topics, showing shifts from biogeography and species classification to phylogenetics and sexual selection. This comprehensive overview underscores the global research efforts and evolving focus areas, aiming to enhance awareness and guide future studies in BoPs conservation.